Sedimentary rare earth elements in Dongting Lake - Zekun Wang; Linghan Zeng; Xuejing Long; Heyuan Wang; Jia Peng; Xu Chen (PANGAEA, 2025)
This dataset presents concentrations of rare earth elements in the sediment core of Dongting Lake. The sediment core is 72 cm in length, and it recorded the history of environmental changes since ~1910 CE according to the 210Pb dating.